Surgical management of macular edema associated with von Hippel-Lindau disease: a case report (Ukrainian Journal of Ophthalmology, 2025)
We report a case of surgical management of macular edema associated with von Hippel-Lindau (VHL) disease. The patient received vitrectomy with angioma endoresection using high-frequency welding of biological tissues. Follow-up findings included complete resorption of hard exudates, improvement in the macular profile and partial restoration of vision. A review of the treatment outcome for this case confirms the efficacy of vitrectomy with endoresection of retinal hemangioblastoma in the management of macular edema associated with VHL disease. Timely diagnostic evaluation and adequate postoperative follow-up are essential for the best treatment outcome.
Keywords: high-frequency electric welding of biological tissues; von Hippel-Lindau disease; vitrectomy; retinal hemangioblastoma; macular edema; retina